Key Components and Contrasts in the Nitrogen Budget Across a U.S.‐Canadian Transboundary Watershed. Issue 9 (29th August 2020) - Lin, Jiajia; Compton, Jana E.; Clark, Chris; Bittman, Shabtai; Schwede, Donna; Homann, Peter S.; Kiffney, Peter; Hooper, David; Bahr, Gary; Baron, Jill S.
Abstract: Watershed nitrogen (N) budgets provide insights into drivers and solutions for groundwater and surface water N contamination. We constructed a comprehensive N budget for the transboundary Nooksack River Watershed (British Columbia, Canada, and Washington, USA) using locally derived data, national statistics, and standard parameters. Feed imports for dairy (mainly in the United States) and poultry (mainly in Canada) accounted for 30% and 29% of the total N input to the watershed, respectively. Synthetic fertilizer was the next largest source contributing 21% of inputs. Food imports for humans and pets together accounted for 9% of total inputs, lower than atmospheric deposition (10%). N imported by returning salmon representing marine‐derived nutrients accounted for <0.06% of total N input. Quantified N export was 80% of total N input, driven by ammonia emission (32% of exports). Animal product export was the second largest output of N (31%) as milk and cattle in the United States and poultry products in Canada. Riverine export of N was estimated at 28% of total N export. The commonly used crop nitrogen use efficiency (NUE) metric alone did not provide sufficient information on farming activities but in combination with other criteria such as farm‐gate NUE may better represent management efficiency. Agriculture was the primary driver of N inputs to the environment as a result of its regional importance; the N budget information can inform management to minimize N losses. The N budget provides key information for stakeholders across sectors and borders to create environmentally and economically viable and effective solutions. Key Points: Nearly 81% of nitrogen (N) inputs to the Nooksack River Watershed were used to support agricultural production, mostly as animal feed About 32% of N export was via ammonia volatilization and 28% via riverine export; 53% of riverine nitrate was from the forested upland Contrasts in farm practices and policies between the United States and Canada were reflected in nutrient management, resulting in different NUEs